Does the Weekly Distribution of Games and Competition Density Affect Training Load in Elite Male Basketball Players Based on their Playing Role? - Hugo Salazar; Luka Svilar; Julen Castellano; Jairo Vázquez-Guerrero; Enrique Alonso Perez-Chao (International Journal of Strength and Conditioning)
Purpose: The aim of this study was to compare the external workload encountered by Euroleague basketball players based on the weekly game density (ranging from 0 to 3-games per week) and player roles (bench, rotation, and starter). Method: A longitudinal observational study was conducted across two full seasons. The weekly workload was determined by recording PlayerLoad™ using microsensors during basketball practices and estimations for games. A linear mixed model with Bonferroni post-hoc tests was used to compare the workload among weeks and player roles. Additionally, Cohen’s d effect sizes were applied to determine the magnitude of the differences. Results: Starting players consistently experienced higher external workload compared to rotation players and bench players across all weekly configurations. In weeks with more games, especially from Friday to Sunday, starters faced the highest workload, followed by rotation players. Significant differences (p<0.05) were observed both in the total number of games per week and in the specific distribution of games within the week. Conclusion: These findings highlight the substantial impact of game density and player roles on the workload experienced throughout a professional men’s basketball season. Therefore, coaches should take this into account when planning appropriate weekly workloads based on players’ roles within the team roster.